Representasi Ekokritik Sastra Perspektif Lawrance Buell dalam Novel Menanam adalah Melawan Karya Widodo - Santi Oktaviani; Moh. Ruddin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research examines literary ecocriticism in the novel Menanam is Melawan by Widodo through the perspective of Lawrance Buell's theory. This research aims to identify and analyze four aspects of literary ecocriticism from Lawrance Buell's perspective in the novel Menanam is Against. The method used is descriptive narrative with a qualitative approach to literary ecocriticism. The data collection technique uses note-reading techniques. Next, data analysis was carried out by organizing, reducing, presenting and drawing conclusions. The results of the research show that the four aspects of literary ecocriticism from Lawrance Buell's perspective are fulfilled. Historical non-human elements are reflected in the phenomenon of destruction of Kulon Progo land elements and phenomena of environmental destruction such as the burning of houses and patrol posts in coastal villages. The legitimacy of the interests of non-human elements towards humans is reflected in the fact that plants provide success with the abundant harvests of the Kulon Progo community and sand provides a connection between the community and the environment. Human responsibility for nature is reflected in the Kulon Progo community making various efforts such as physical responsibility, intellectual responsibility, and spiritual responsibility. The dynamics of nature are reflected in the occurrence of negative dynamics, namely the conversion of coastal land into iron sand mining areas and positive dynamics, namely land conversion. The shaky and barren land became fertile agricultural land.